The potential of landscape design elements for crime prevention in a residential neighbourhood / Zuraidah Shaari - Shaari, Zuraidah (2015)
Safe residential neighbourhood areas are the most important elements of safe cities. As crime rates keep on increasing, safety issues has been taken into consideration in housing planning all over the world. Design elements can play a significant role in reducing crime and these elements can be implemented as a variety of design functions for crime prevention in residential neighbourhood. Design elements are the combination of nature and construction components of living elements, natural elements, human elements and abstract elements. They include vegetation, fences and barriers, lightings, pathways, signage, guard houses, access, playground facilities, parking, bus stop and good maintenance. Hence, this study is to determine the design elements based on three (3) objectives: to identify the design elements that can reduce crime in the residential neighbourhood; to identify the characteristics of the design elements in reducing crime; and finally to recommend selected elements for crime reduction in residential neighbourhood. The concept of defensible space was developed for the public housing environment. It is similar to CPTED (Crime Prevention through Environmental Design) in that it shares the basic characteristics of natural surveillance, natural access control and territorial concern. The study area is located at USJ 6, Subang Jaya. Finally, the results obtained were analysed using the Statistical Package for Social Sciences (SPSS). The findings of this research concluded that design elements (i.e., vegetation; fences and barriers; lightings; pathways; signage; guard houses; and good access), are important components in reducing crime. Environmental designs help the community in residential areas to be free from crime. Residents believed that gated housing, target hardening, functioning lightings, and regular maintenance schedule improved security in neighbourhood. Social activities such as neighbourhood watch program and attending meetings about safety issues will increase the awareness to create a safer community.Furthermore, social interaction becomes the most essential part especially to develop an effective surveillance by residents. The proper placement of design elements within the residential neighbourhood can provide opportunities for improvement in the quality of life and safety.